2020
DOI: 10.2217/nnm-2019-0349
|View full text |Cite
|
Sign up to set email alerts
|

Antihepatoma Activity of Multifunctional Polymeric Nanoparticles Via Inhibition of Microtubules and Tyrosine Kinases

Abstract: Aim: Synthesis of poly-L-lactic acid nanoparticles comprising of microtubule-inhibitor docetaxel and tyrosine kinase inhibitor sorafenib (PLDS NPs) for hepatoma treatment. Materials & methods: PLDS NPs were prepared by the emulsion solvent evaporation method and the anticancer activity was evaluated in Huh7 hepatoma cells. Results: Real-time imaging of quantum dots incorporating poly-L-lactic acid nanoparticles showed a rapid internalization of the nanoparticles in Huh7 cells. PLDS NPs exerted stronger ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…The antitumor effect of So can also occur due to the inhibition of the RAF/MEK/ERK signaling cascade [ 31 ], which was also observed in our experiments, but with greater efficiency when using selenium nanoparticles. It has been shown on Huh7 hepatoma cells that the IC 50 for sorafenib in the efficiency of cell cycle arrest is 15 ± 1.4 µM, and for SeNPs it is 5 ± 2 µg/mL, while doping of SeNPs with sorafenib leads to a decrease in IC 50 to 820 ± 26 nM [ 34 ]. It was also shown on Huh7 cells that So in the effective concentration range of 15–30 μM causes a significant percentage of necrotic cell death (10.5–18%), while SeNPs at concentrations of 5–10 μg/mL are characterized by less pronounced necrosis (6–11%) [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The antitumor effect of So can also occur due to the inhibition of the RAF/MEK/ERK signaling cascade [ 31 ], which was also observed in our experiments, but with greater efficiency when using selenium nanoparticles. It has been shown on Huh7 hepatoma cells that the IC 50 for sorafenib in the efficiency of cell cycle arrest is 15 ± 1.4 µM, and for SeNPs it is 5 ± 2 µg/mL, while doping of SeNPs with sorafenib leads to a decrease in IC 50 to 820 ± 26 nM [ 34 ]. It was also shown on Huh7 cells that So in the effective concentration range of 15–30 μM causes a significant percentage of necrotic cell death (10.5–18%), while SeNPs at concentrations of 5–10 μg/mL are characterized by less pronounced necrosis (6–11%) [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown on Huh7 hepatoma cells that the IC 50 for sorafenib in the efficiency of cell cycle arrest is 15 ± 1.4 µM, and for SeNPs it is 5 ± 2 µg/mL, while doping of SeNPs with sorafenib leads to a decrease in IC 50 to 820 ± 26 nM [ 34 ]. It was also shown on Huh7 cells that So in the effective concentration range of 15–30 μM causes a significant percentage of necrotic cell death (10.5–18%), while SeNPs at concentrations of 5–10 μg/mL are characterized by less pronounced necrosis (6–11%) [ 34 ]. In our experiments, it was found that SeSo practically suppresses necrotic processes in HepG2 cells, predominantly causing apoptosis, especially at its early stages, at lower concentrations (for SeNPs, 2.5 µg/mL, for SeSo, 0.5 µg/mL).…”
Section: Discussionmentioning
confidence: 99%
“…QDs-based signal probes are of great interest and have been tested in numerous biotechnological applications. Some of the early and most successful uses of QDs have been in immunofluorescence labeling of fixed cells and tissues (15,16), immuno-staining of membrane proteins (17,18), microtubules (19), nuclear antigens (20,21), and fluorescence in situ hybridization of chromosomes or combed DNA (22, 23) (Figure 3).…”
Section: Qds For In Vitro Diagnosis and Imagingmentioning
confidence: 99%